2009
DOI: 10.1557/jmr.2009.0008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of synthesis of the solid solution, Pb(Zr1–xTix)O3 on a single substrate using a high-throughput modified molecular-beam epitaxy technique

Abstract: Synthesis of Pb(Zr 1-x Ti x )O 3 (PZT) on a single substrate using a high-throughput molecular-beam epitaxy technique was demonstrated. In situ synthesis of crystalline PZT at elevated substrate temperatures could not be achieved, as reevaporation of Pb (PbO) occurred and the partial pressure of O 2 was insufficient to prevent formation of a PbPt x phase during deposition. Instead, ex situ postdeposition annealing was performed on PZT deposited at room temperature. Dense single phase PZT was prepared with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The physical methods include sputter deposition, 2729 pulsed laser deposition (PLD), 3033 molecular beam epitaxy (MBE), 34 and evaporation. 35,36 The chemical methods are metal–organic chemical vapor deposition, 37,38 plasma enhanced chemical vapor deposition, 39,40 and sol–gel processing.…”
Section: Introductionmentioning
confidence: 99%
“…The physical methods include sputter deposition, 2729 pulsed laser deposition (PLD), 3033 molecular beam epitaxy (MBE), 34 and evaporation. 35,36 The chemical methods are metal–organic chemical vapor deposition, 37,38 plasma enhanced chemical vapor deposition, 39,40 and sol–gel processing.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used for the last ten years to probe the relationship between composition, structure and key figures of merit of selected perovskites. As exemplified in this paper, perovskites used for piezoelectricity, such as PbxZryTi1-yO3-δ 77,78 and BixNd1-…”
Section: Perovskites Systems Studied By Ht-epvdmentioning
confidence: 99%
“…B-site substitution studies have focussed on studying the PbxZryTi1-yO3-δ solid solution for piezoelectric materials 77,78 and LaxMnyNi1-yO3δ and SrxTi1-yFeyO3-δ as electrocatalysts. 4,5 Please do not adjust margins…”
Section: B-site Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al [1] have reported PbPt 2 O 4 formation at the interface between lead-zirconate-titanate (PZT) solid solution and Pt during PZT deposition using high-throughput modified molecular-beam epitaxy (MBE) technique. There are three known ternary oxides in the Pb-Pt-O system; Pb 2 Pt 2 O 6.5 , Pb 2 PtO 4 and PbPt 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%